Omnichannel Strategy and Student Word of Mouth in Higher Education - Cicilia Sriliasta; Bahtiar Usman; Ayu Ekasari; Noah Rangi (Pandawan, 2026)
In the era of digital transformation, Higher Education Institutions (HEIs) face increasing pressure to modernize their service delivery to meet evolving student expectations. While Omnichannel Integration (OCI) has revolutionized customer experiences in retail and banking, its application within the educational sector remains underexplored. This systematic literature review aims to bridge this gap by examining the impact of OCI on Student Engagement and Word-of-Mouth (WoM). Adhering to the PRISMA guidelines, a rigorous screening process was conducted across multiple academic databases, resulting in the analysis of 74 eligible studies published between 2014 and 2024. The thematic analysis identifies four core dimensions of OCI Channel Service Configuration, Content Consistency, Quality Assurance, and Process Consistency. The findings reveal a significant distinction between commercial and educational contexts in HEIs, the integration of physical and digital touchpoints is not merely a logistical upgrade but a strategic necessity for relationship building. Crucially, the review establishes that OCI does not automatically generate advocacy. Instead, the student engagement acts as a vital mediating variable, meaning that seamless integration fosters deeper engagement, which subsequently drives positive WoM. This study contributes to the literature by synthesizing fragmented evidence into a cohesive framework, offering university administrators practical strategies to enhance student retention and institutional reputation through consistent cross channel experiences.